Implementasi Program One Day One Juz dalam Meningkatkan Tahsinul Quran di Era Digitalisasi Guru Quran SMPIT Daarul Hikmah Boarding School Bontang Tahun Pelajaran 2023/2024 - Sugiarsih, Rina; Parmono, Parmono (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
The objective of this research is to evaluate the implementation of the One Day One Juz (ODOJ) program and to assess the improvement in Quranic recitation (Tahsinul Quran) among Quranic teachers. The approach used in this study is a descriptive qualitative system. Data were collected through in-depth interviews, direct observations, and document analysis. The subjects of the research are Quranic teachers involved in the ODOJ program. Interviews were conducted to gather information on the experiences, perspectives, and challenges faced by teachers in implementing this program. The results indicate that the ODOJ program has had a significant positive impact on the improvement of Quranic recitation among teachers. Digital technology, such as Quranic apps and social media, has been highly beneficial in the execution of this program. Additionally, interactions through WhatsApp groups have enhanced teachers' motivation and commitment to achieving their daily targets. Based on these findings, it can be concluded that ODOJ has successfully improved the Quranic recitation skills of the teachers, supported by digital technology and social media interactions, particularly through WhatsApp groups.